FEATURES OF ORGANIZATIONAL CULTURE IN THE WOMEN’S LABOR COLLECTIVE - Kurapova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to one of the topical in modern management the problem of organizational culture. The problem of organizational culture is currently of increased interest in connection with the solution of practical problems of increasing the efficiency of organizations, taking into account the human factor. The basis of the life potential of an organization is its organizational culture, which involves certain ways and forms of people’s activities, based on a specific system of values, norms, ideals of both the organization and society as a whole. The activity of modern organizations depends on many factors, including the gender composition of the organization and the level of general and professional culture of employees, their personal profile.Therefore, the purpose of this research was to study the insufficiently investigated aspect of this problem - the features of the organizational culture in the women’s labor collective. The main method was chosen test method. The study was conducted using the method OCAI (Organizational Culture Analyze Instrument) by C. Cameron, R. Quinn, which allows to determine both the existing and the preferred type of organizational culture.As a result, differences in the profiles of organizational culture in the women's labor collective are shown, compared with the men's labor collective: the current state is characterized by the prevalence of hierarchical organizational culture and a slight severity of indicators of market and clan organizational cultures.It was found that the current state of the organizational culture is not satisfactory for the employees of the organization, preference is given to the clan and adhocratic types of organizational culture and the values of the hierarchical organizational culture currently expressed are rejected.Thus, the organizational culture is determined by the gender characteristics of the employees of the organization and is manifested in their values, norms of behavior and attitudes.